THE EFFECT OF CUTTING SPEED ON SURFACE ROUGHNESS IN THE TURNING PROCESS OF AISI 1045 CARBON STEEL USING KOBE M2 HSS CHISELS - Tarigan, Bersyeba; Rasyid, Muksin; Supriono (PT Inovasi Pratama Internasional, 2024)
The purpose of this multilevel shaft turning performance is to analyze the specimen used, namely medium carbon steel alloy and get good workpiece results, knowing the ductility of the workpiece by adjusting the tool blade, speed, time, depth of cut, and surface roughness. The research method used is the impact test method to see the results of the influence of strong currents in steel joints. The results of this study are cutting speed is very influential on the results of the surface roughness of the test material, can be seen from the data analysis and research results. The surface of the test material with the highest level of smoothness is obtained from the use of the lowest cutting speed (100 m/min) with a roughness level of (4.1). The highest roughness level (7.1) with the cutting speed used (200 m/min). The higher the cutting speed used, the greater the price of the surface roughness value obtained or produced. However, the wear of the tool blade used is likely to also affect the level of surface roughness. Geram income depends on the cutting speed, the greater the feeding motion used, the greater the thickness of the resulting geram. The smaller the cutting speed used, the smaller the resulting furrow.